Andrological emergencies in current emergency medicine: A narrative overview of clinical, psychological, and worldwide implications - Ghada Farouk Mohammed; Mohammed Saleh Al-Dhubaibi; Saleh Salem Bahaj; Ahmed Mohammed Al-Dhubaibi; Sameh Saad Aziz; Yasser Salem N. Saleh (Urologia Journal, 2026)
Background: Andrological emergencies (AEs) constitute a critical subset of acute urogenital conditions requiring urgent recognition and intervention to preserve sexual and reproductive function while preventing long-term morbidity. Common AEs include testicular torsion, ischemic priapism, penile fracture, paraphimosis, Fournier’s gangrene, penile strangulation, and acute urinary retention. Aim: To provide a comprehensive synthesis of current knowledge on the clinical presentation, diagnostic approaches, therapeutic strategies, psychosocial implications, ethical considerations, and global disparities. Methods: A narrative review of peer-reviewed literature was conducted across major medical databases. Evidence was integrated thematically to highlight clinical features, diagnostic tools, management strategies, and broader psychosocial and health system impacts. Outcomes: Key outcomes included improved understanding of diagnostic accuracy, therapeutic efficacy, psychosocial burden, ethical considerations, and inequities in access to timely care. Results: AEs present across all age groups with distinct clinical signs necessitating rapid recognition. Doppler ultrasound and timely surgical intervention remain central for testicular torsion, while aspiration with intracavernosal sympathomimetics represents first-line management for ischemic priapism. Early surgical repair is essential in penile fracture and paraphimosis. Delayed presentation, often due to stigma and embarrassment, significantly worsens prognosis. Ethical challenges, particularly regarding informed consent in emergencies, are frequently encountered. Global disparities in healthcare access and provider training contribute to heterogeneous outcomes, particularly in low-resource settings. Clinical implications: Optimal management of AEs requires multidisciplinary expertise, incorporation of sensitive psychosocial care, and equitable access to emergency services. Strengths and limitations: This review integrates clinical, psychosocial, ethical, and global health perspectives on AEs, offering a holistic view. However, reliance on heterogeneous data and limited comparative studies constrain definitive conclusions. Conclusion: The timely recognition and management of AEs are essential to preserve function and quality of life. Addressing psychosocial barriers, ethical complexities, and healthcare disparities will require patient-centered education, enhanced provider training, and international collaboration to establish standardized, globally adaptable emergency protocols.